2009
DOI: 10.1002/btpr.367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disaccharides on the stabilization of bovine trypsin against detergent and autolysis

Abstract: Osmolytes have been reported to stabilize biomolecules and even whole organisms against exposure to adverse environmental conditions. In this work, we report for the first time the use of some of these osmolytes, viz., the disaccharides trehalose and sucrose, in the stabilization of bovine trypsin against exposure to the anionic detergent sodium dodecyl sulfate and autolysis. Exposure of trypsin to SDS at a molar ratio of 1:45 led to decrease in trypsin activity by 61%. In the presence of 1 M sucrose and 1 M t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Porter and Peterson also observed this phenomenon, as the SDS-induced trypsin and chymotrypsin denaturation is slowed in presence of macromolecular substrates (34). There are also data in the literature that suggests that the addition of a sucrose, trehalose, or trypsin inhibitor to trypsin solutions may minimize the destabilizing effect of SDS and reduced the trypsin autoproteolysis (33,35).…”
Section: Effect Of Ionic Surfactants On Pancreatin Proteolytic Activitymentioning
confidence: 81%
See 1 more Smart Citation
“…Porter and Peterson also observed this phenomenon, as the SDS-induced trypsin and chymotrypsin denaturation is slowed in presence of macromolecular substrates (34). There are also data in the literature that suggests that the addition of a sucrose, trehalose, or trypsin inhibitor to trypsin solutions may minimize the destabilizing effect of SDS and reduced the trypsin autoproteolysis (33,35).…”
Section: Effect Of Ionic Surfactants On Pancreatin Proteolytic Activitymentioning
confidence: 81%
“…It appears that the thermal treatment of the samples increased the unfolding rate of the proteinases that comprise the pancreatin. In comparison, Prasad et al reported that a 30-min incubation of trypsin at room temperature with various amounts of SDS (trypsin/SDS ratio from 1:10 to 1:80) reduced its initial activity by 61% (33).…”
Section: Effect Of Ionic Surfactants On Pancreatin Proteolytic Activitymentioning
confidence: 99%
“…8(a), the CD spectra (molar residue ellipticity (u) versus wavelength) of commercial trypsin in water exhibited a minimum around 208 nm and there was a hump around 220-222 nm wavelength for both spectra denoting the existence of a-helix, since bovine trypsin is a protein consisted of a-helix, b-sheet, b-turn and random coil (Ghosh, 2008). Although the general spectral shape remained, the ellipticity of processed trypsin at $208 nm and 210-220 nm band was reduced to nearly half the value of the native protein, indicating a structural perturbation of the above secondary structures (Prasad and Roy, 2010;Simon et al, 2001). Fig.…”
Section: Protein Structural Stability and Enzymatic Activitymentioning
confidence: 84%
“…The maximum intensity of emission spectrum of commercial trypsin was observed at $340 nm. No red shift of the peak occurred, but the intensity of the spectra of processed trypsin decreased in comparison with the native curve, which meant that the microenvironment of the tryptophan and tyrosine residues was altered to some degree after SAA-HCM processing (Prasad and Roy, 2010). From the above discussion, the potential variations of trypsin molecular were implied, which might affect the biological activity of the enzyme.…”
Section: Protein Structural Stability and Enzymatic Activitymentioning
confidence: 93%
“…The two domains of trypsin comprised mainly H-bonded crossed β-sheet networks. One of the sheets positioned the catalytic Ser correctly in the active site, whereas the second sheet formed a part of the substrate recognition cleft [27]. It could be inferred that β-sheet of trypsin bound directly to the TiO 2 nanoparticles, and the press and pull strength twisted the sheets, which further resulted in the inactivation of trypsin.…”
Section: Tem Detectionmentioning
confidence: 99%